2014
DOI: 10.1902/jop.2013.130117
|View full text |Cite
|
Sign up to set email alerts
|

Saliva and Serum Levels of B‐Cell Activating Factors and Tumor Necrosis Factor‐α in Patients With Periodontitis

Abstract: Within the limits of this study, it may be suggested that elevated salivary and serum TNF-α, APRIL, and BAFF in patients with periodontitis may contribute to the dominance of B cells in periodontitis lesions. Moreover, higher levels in healthy smokers than non-smoking counterparts may play a role in detrimental effects of smoking on periodontal tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
55
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 56 publications
9
55
0
5
Order By: Relevance
“…However, inclusion of both current and former smokers may be regarded as a limitation of the present study, as smoking can affect both salivary and serum cytokine levels [24]. On the other hand, the numbers of current/former smokers appeared to be balanced in the study groups and similar effects of smoking might be expected on the biochemical measurements in each study group.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, inclusion of both current and former smokers may be regarded as a limitation of the present study, as smoking can affect both salivary and serum cytokine levels [24]. On the other hand, the numbers of current/former smokers appeared to be balanced in the study groups and similar effects of smoking might be expected on the biochemical measurements in each study group.…”
Section: Discussionmentioning
confidence: 85%
“…Increased levels of inflammatory markers have been proposed to have a role in periodontal disease and on interactions with systemic diseases [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is likely that APRIL detected in the gingival epithelium was locally produced in response to dental plaque bacteria. An additional possibility is that APRIL might be in part systemically derived, although the serum levels of APRIL in patients with chronic periodontitis are not significantly higher than those of healthy controls (44). The APRIL-rich zone within the gingiva was similar to that previously described in mucosa-associated lymphoid tissues (24).…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study reported on the presence of APRIL and BLyS in the serum and saliva of patients with chronic periodontitis and healthy controls (44). Although BLyS was detected at significantly higher concentrations in both fluids from patients relative to controls, there were no statistically significant differences in the levels of APRIL between the two groups (44).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a strong relationship was found among serum levels of IL-32 and the gingival IL-32 levels and the serum levels of IL-6, as well as the alveolar bone and attachment loss. It was previously demonstrated that IL-32 was considerably upregulated by the periodontal pathogens, P.gingivalis and Fusobacterium nucleatum, in an oral epithelial cell line H400 (30). Moreover, IL-32 was expressed by monocytes via P.gingivalis-derived LPS and supposedly IL-32 is a factor that leads to the formation of periodontal disease (15).…”
Section: Discussionmentioning
confidence: 98%